Low-energy particle experiments–ion mass analyzer (LEPi) onboard the ERG (Arase) satellite - Asamura, K.; Kazama, Y.; Yokota, S.; Kasahara, S.; Miyoshi, Y. (Earth, planets, and space, 2018)
Low-energy ion experiments–ion mass analyzer (LEPi) is one of the particle instruments onboard the ERG satellite. LEPi is an ion energy-mass spectrometer which covers the range of particle energies from < 0.01 to 25 keV/q. Species of incoming ions are discriminated by a combination of electrostatic energy-per-charge analysis and the time-of-flight technique. The sensor has a planar field-of-view, which provides 4 π steradian coverage by using the spin motion of the satellite. LEPi started its nominal observation after the initial checkout and commissioning phase in space.